Covid-19 and Sustainable Tourism: Macroeconomic Effect and Policy Comparison among Europe, the USA and China - Islam, Mohammad Monirul; Fatema, Farha (Asian Business Review, 2020)
This study examines the potential macroeconomic effects of Covid-19 on the tourism sector of Europe, the USA, and China as well as provides policy suggestions in light of previous scholarly works. The study finds that the global tourism sector is geocentric and the tourism sector of EU countries is interdependent. The study also finds strong domestic tourism in the USA and China whereas domestic tourism in EU countries is not that strong. As domestic tourism is less income-elastic than international tourism countries should promote domestic tourism to recover the loss of this sector from the adverse effect of Covid-19. Although the probable loss of the tourism sector can be estimated with reference to the recent previous global economic crises, the study assumes far-reaching and massive effects of Covid-19 on the tourism sector due to strictly restricted or banned global and domestic travel as well as the unknown duration of the pandemic. The study also finds the similarity of age groups participating in tourism and infected and died by Covid-19. So, combined and comprehensive policies should be formulated to save the international tourism sector from the drastic catastrophe of Covid-19.